Implementation of AI-Based TikTok Content Marketing to Increase Sales: A Study of MSMEs X - Athhar Malika Yudistira Prasetyo; Ratih Purbasari; Mas Rasmini (Indonesian Journal Economic Review (IJER), 2026)
The rapid growth of the global edutech industry has encouraged MSMEs to strengthen digital marketing strategies. X Edutech, an MSME specializing in artificial intelligence education, previously relied mainly on paid Facebook Ads and had not utilized TikTok as a marketing channel. This study aimed to analyze the initial marketing condition, implement an AI-assisted TikTok content strategy, and evaluate its associated marketing and sales outcomes. A qualitative project-based applied research approach was employed using Pulizzi's (2014) six-stage content marketing framework. Data were collected through observation, semi-structured interviews, documentation, literature review, and open-ended questionnaires. SWOT analysis and the Value Proposition Canvas were used to identify marketing opportunities. The implementation involved developing a content strategy, establishing a TikTok account, creating a content calendar, and publishing 36 AI-assisted content pieces over two months. The implementation generated 538 followers, 32,877 views, 84 leads, 29 inquiries, and 55 sales attributed to TikTok. Transactions increased from 144 to 207, while revenue increased by 43.75%. These findings indicate an association between the implementation and improved marketing and sales indicators. However, the changes cannot be attributed solely to AI-assisted TikTok marketing because Facebook Ads, TikTok Ads, and other activities continued during the project.